Distribution and Genetic Diversity of the Korean Foliicolous Lichen, Strigula depressa - Seung-Yoon Oh; Jung-Jae Woo; Jae-Seoun Hur (Mycobiology)
Foliicolous lichens, such as Strigula depressa, are increasingly recognized as potential indicators of subtropical ecosystem dynamics due to their sensitivity to climatic conditions, with climate change likely to expand their distribution in the South Korea. Despite their ecological importance, studies on the distribution and genetic structure of S. depressa in South Korea remain limited. This study aims to examine this knowledge gap by analyzing the ecological preferences, genetic diversity, and distribution change of S. depressa under future climate scenarios. Field surveys were conducted across 96 sites, including 66 sites on Jeju Island and 30 islands, revealing a highly restricted distribution with the species present at only 12 sites in four islands. Analysis of bioclimate variables indicated that warmer temperatures and lower temperature seasonality significantly influence the distribution of S. depressa. Population genetic analyses, based on ITS sequences from 45 samples, identified 17 haplotypes and revealed moderate regional differentiation, with significant isolation-by-distance but no isolation-by-environment effect. Species distribution modeling predicts potential range expansion under future climate scenarios. These findings highlight the ecological sensitivity of S. depressa to temperature gradients and its potential as a bioindicator for subtropical ecosystem shifts, emphasizing the need to conserve genetically diverse populations to enhance resilience against climate change.